PENGARUH PENERAPAN STANDAR AKUNTANSI PEMERINTAHAN DAN KOMPETENSI SUMBER DAYA MANUSIA TERHADAP KUALITAS LAPORAN KEUANGAN DI KEMENTERIAN AGAMA KABUPATEN TASIKMALAYA - Pian Ramdan; Cepi Juniar Prayoga; Fithri Sri Mulyani (Jurnal Riset Keuangan dan Akuntansi, 2021)
This study aims to measure the effect of Governmental Accounting Standards and Human Resources Competence on the Quality of Financial Statements. The population in this study were all employees of the Ministry of Religion of Tasikmalaya Regency. The sample in this study used a total sampling technique. The method used in this research is descriptive analysis method with a case study approach which tries to examine the causal relationship or the cause and effect of the variables in the case. These results indicate that partially the application of government accounting standards and human resource competence has a positive effect on the quality of financial reports. The results of the research simultaneously show that the application of government accounting standards and competence of resources has a positive effect on the quality of financial reports. Keywords: Competence, Implementation of Government Accounting Standards, Quality of Financial Statements